2003
DOI: 10.3189/172756403781815537
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of the flow rates of debris-laden ice

Abstract: Ice-sheet basal ice is warmer than that above because of the heat from the Earth’s interior. The stresses acting on the basal ice are greatest. In addition, the basal ice often contains debris consisting of silt and small stones picked up from the rock over which the ice flows. Because the base is the warmest part of an ice sheet and the stress there is greatest, flow rates in the basal ice are large and often contribute most of the ice movement. It is therefore important, for accurate modelling of the ice she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
12
1
Order By: Relevance
“…(For sand/silt fractions in excess of 50%, there does seem to be a clear correlation between stiffness and debris content (Mangold and others, 2002)). We speculate that the difference between our conclusion and that of Jacka and others (2003) reflects the radical difference between a laboratory experiment and the natural ‘ice-squeezing’ experiment performed by the Mount St Helens lava dome, and in particular the associated scale effects. In the laboratory, because the grain size of the ice is likely to be comparable to the grain size of the debris, the presence of thin water films at ice–debris interfaces probably facilitates regelation and other deformation mechanisms.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…(For sand/silt fractions in excess of 50%, there does seem to be a clear correlation between stiffness and debris content (Mangold and others, 2002)). We speculate that the difference between our conclusion and that of Jacka and others (2003) reflects the radical difference between a laboratory experiment and the natural ‘ice-squeezing’ experiment performed by the Mount St Helens lava dome, and in particular the associated scale effects. In the laboratory, because the grain size of the ice is likely to be comparable to the grain size of the debris, the presence of thin water films at ice–debris interfaces probably facilitates regelation and other deformation mechanisms.…”
Section: Discussioncontrasting
confidence: 79%
“…If flow of the debris-laden East Crater Glacier at Mount St Helens is properly characterized by Glen’s flow law with n = 3, then the ice must be stiffer than debris-free ice by a factor of 5 to 10, with the stiffness increasing as the rock-debris content rises. This inference from modeling contrasts with the discussion by Jacka and others (2003), who reviewed laboratory data and concluded that there is no relation between deformation rate and debris (sand) content for debris fractions up to 15% by volume. (For sand/silt fractions in excess of 50%, there does seem to be a clear correlation between stiffness and debris content (Mangold and others, 2002)).…”
Section: Discussionmentioning
confidence: 68%
“…In some studies it exhibits characteristics that are “softer” than those of debris‐free glacier ice [ Lawson , 1996], perhaps facilitated by higher liquid contents promoted by the presence of dissolved salts. The results of other studies find no affect on flow rate of sediment concentrations up to 15% by volume [e.g., Jacka et al , 2003]. By contrast, deformation tests on frozen sediments from the base of Suess Glacier, Antarctica, indicate a peak shear strength that is nearly twice that of glacier ice samples [ Fitzsimons et al , 2001].…”
Section: Consequences For Simple Glacier Systemsmentioning
confidence: 95%
“…Further evidence supporting this has been provided by Baker and Gerberich [], Yasui and Arakawa [], and Song et al [], among others. On the other hand, creep experiments conducted by Jacka et al [] failed to show any systematic change in creep rate as debris concentration was varied from 0 to 14.5% by volume at −12°C and 130 kPa.…”
Section: Experimental Constraintsmentioning
confidence: 99%
“…However, several other widely cited field studies indicate precisely the opposite: addition of debris weakens ice such that it deforms more rapidly than clean ice under similar conditions [ Fisher and Koerner , ; Echelmeyer and Zhongxiang , ; Cohen , ]. Still other observations suggest that ice rheology is largely unaffected by the presence of modest concentrations of debris inclusions [ Cuffey et al, ; Jacka et al, ]. Together, these observations along with many others raise question about the validity of the generalization above.…”
Section: Introductionmentioning
confidence: 99%